Analytical solution for mechanical behavior characterization of sandy dolomite tunneling - Sun, Di; Tao, Zhigang; Yang, Hong; Shui, Haoche; Lei, Xiaotian; Wang, Fengnian; Huo, Shusen; Shu, Hang; Xia, Weitong; Wang, Zhaoxi; He, Manchao (Frontiers in Earth Science, 2024)
Tunneling in sandy dolomite strata is often faced with hazards such as collapse, water inrush, and water-sand inrush, which seriously threaten the safety of tunnel construction. Currently, there are limited studies on the mechanical behaviors of sandy dolomite tunnel. In view of this, an analytical solution for tunneling in sandy dolomite strata is derived, and then the parametric analysis is performed to analyze the mechanical response of rock mass in sandy dolomite tunnels. The results demonstrate five tunnel sidewall stress scenarios according to the different lateral pressure coefficients (λ). Varying λ values impacted stress distribution and tunnel stability, with extreme values posing instability risks. The safety of tunnel is greatly reduced when the rock stress approaches the plastic limit. At different internal friction angle, cohesion, and initial rock stress, the radial stress decreases gradually as the radius increases. The stress values under different conditions tend to be similar, while the effects of internal friction angle, cohesion, and initial rock stress on the stress in elastic zone decrease with increasing distance from the center of the tunnel. Under different internal friction angles and cohesion, the radius of plastic zone increases with the increasing distance from the excavation surface, and a larger internal friction angle and cohesion lead to an increase in stress. The stress and cohesion of rock mass significantly affect the radius of plastic zone, and an increase in tunnel excavation radius also leads to an increase in radius of plastic zone. These findings provide reference and insight for similar geotechnical engineering practices in the future.